2009
DOI: 10.1179/joc.2009.21.4.414
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Daptomycin in the Treatment of Osteomyelitis: Results from the CORE®Registry

Abstract: Antibiotic safety is a major determinant in osteomyelitis therapy. Limited data is available describing the long-term safety and efficacy of daptomycin. the safety population was drawn from CORE 2005 and 2006, a retrospective, observational, multicenter study. Clinically evaluable patients received >3 days of daptomycin appropriately adjusted for renal function. three hundred twenty-seven patients were evaluated for safety; 188 (57%) >or=6 mg/kg, 139 (43%) <6 mg/kg. Thirty-one (10%) patients experienced advers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 15 publications
3
19
0
Order By: Relevance
“…Although the increases in CPK observed with both the 6-and 8-mg/kg doses of daptomycin in this study were numerically higher than those seen with the comparator group, they are consistent with other clinical trials of daptomycin at Ն6 mg/kg, where 2.5% to 8.3% of patients experienced CPK elevations (6,9,11,14). Most CPK elevations in our study were of short duration and did not result in musculoskeletal symptoms.…”
Section: Discussionsupporting
confidence: 79%
“…Although the increases in CPK observed with both the 6-and 8-mg/kg doses of daptomycin in this study were numerically higher than those seen with the comparator group, they are consistent with other clinical trials of daptomycin at Ն6 mg/kg, where 2.5% to 8.3% of patients experienced CPK elevations (6,9,11,14). Most CPK elevations in our study were of short duration and did not result in musculoskeletal symptoms.…”
Section: Discussionsupporting
confidence: 79%
“…In the Cubicin Outcome Register and Experience (CORE), <6 mg/kg vs. ≥6 mg/kg daily doses have been compared in patients treated for osteoarticular infections mostly due to S. aureus in, respectively, 139 and 188 patients. No significant differences in terms of clinical efficacy (90% vs. 96%, respectively) were observed [58]. In the European CORE (EUCORE) study, similar results were found in patients treated for osteomyelitis with 6.2-8 mg/kg [success rate, 82% (23/28)] and 4-6.2 mg/kg and [success rate, 75% (130/174)] [59].…”
Section: Clinical Data Justifying the Use Of High Dosessupporting
confidence: 76%
“…The lack of an impressive change in the mean probabilities of clinical success and decreased susceptibility was expected, as the daptomycin AUC and, thus, dose would need to more than double (e.g., the dose would need to increase from 6 to 12 mg/kg/day) to provide exposures adequate to cover a 1-dilution increase in the MIC. Increasing numbers of reports and amounts of data from clinical studies provide support for the use of higher doses of daptomycin (8 to 12 mg/kg/day) to improve outcomes among patients with serious and life-threatening infections (21)(22)(23)(24)(25)(26). The results of simulations conducted to evaluate the mean probabilities of favorable outcomes with daptomycin at 8 and 10 mg/kg/day should be interpreted with some caution since the exposures and model-predicted probabilities estimated were at or beyond those for the exposure range studied; thus, some degree of extrapolation was required.…”
Section: Discussionmentioning
confidence: 99%